Serviceology for Smart Service System Selected papers of the 3rd International Conference of Serviceology - Sawatani, Yuriko; Spohrer, James; Kwan, Stephen; Takenaka, Takeshi (Springer Japan : Imprint: Springer, 2017)
Services are key activities in a globalized economy and they also underlie the quality of life of local residents. The advanced work presented in this book was selected from the proceedings of the Third International Conference on Serviceology (ICServ2015), held July 7-9, 2015, in San Jose, CA, USA. The conference was supported by the Society for Serviceology. The society was established in 2012 in Japan to explore the scientific systematization of services and to promote technological developments for solutions to industrial issues. This book provides a useful general guide to the state of the art in the theory and practice of services. It can also serve as a valuable reference book for researchers in a wide range of fields from engineering to marketing and economics.